Formação de professores de educação física na secretaria de estado da educação de São Paulo - Leme Filho, Alípio da Silva (2017)
The object of study of this research is the investigation of the processes carried out in the SEESP, addressing the continuing training of Physical Education teachers. The objective of this study is to analyze the process of continuous formation initiated by the researcher, from 2003 to 2011, and his interfaces with the procedures used in this training course - the teacher as a trainer and the teacher as formed by the State Secretariat of Education addressing Physical Education under Perspective of a methodological analysis of the teaching and learning processes, starting from the authors that refer to the SEESP Curriculum. In addition, we intend to contribute to the understanding of the possibilities that these training methods triggered in DE 1 bring to the researches in Education, evidencing the production existing in the State Public Network of the State of São Paulo, its changes in the contents and how it is approached. Discipline in accordance with the current curriculum. It also intends to demonstrate the important strategies and contents used in the elaboration of the training processes and pedagogical practices, addressing the forms and how the training course of Physical Education teachers in the Eastern Region 1 - SEESP. The analysis of the contents from 2003 on wards can indicate the paths that are being pursued in this period up to the year 2011, and which pedagogical practices are used and presented to the teachers in the moments of continuous formation. The studies starting from authors, in Education and Physical Education, as biographical methods, contributes to an Education in which are articulated the possibilities of developing a work of continuous formation of teachers and how constitutes the construction of a teaching identity in the school daily, More specifically, in Physical Education classes, that is, how the teacher appropriated these contents received in the training and how they were applied in class in the day to day school. This Teaching perspective can be considered as an advance in contributing to the productions of content of continuous training of teachers, in the production of didactic materials and to innovate the pedagogical practices. The research methodology used was Documentary Analysis. This analysis enabled us to organize the formative contents, establishing a chronology of formation, presenting the researcher's training moments by SEESP and how the formation process of the EFE teachers in the DE 1 was performed. As a result of this research, we highlight a clear construction of Knowledge of the teachers of EFE in their teaching practices, based on the curriculum of the discipline, observed in the analyzes of the questionnaires carried out after the moments of continuous training.